Biomolecules to Biomarkers? U87MG Marker Evaluation on the Path towards Glioblastoma Multiforme Pathogenesis - Pokorná, Markéta; Kútna, Viera; Ovsepian, Saak V; Matěj, Radoslav; Černá, Marie; O'Leary, Valerie Bríd (Pharmaceutics, 2024)
The heterogeneity of the glioma subtype glioblastoma multiforme (GBM) challenges effective neuropathological treatment. The reliance on in vitro studies and xenografted animal models to simulate human GBM has proven ineffective. Currently, a dearth of knowledge exists regarding the applicability of cell line biomolecules to the realm of GBM pathogenesis. Our study's objectives were to address this preclinical issue and assess prominin-1, ICAM-1, PARTICLE and GAS5 as potential GBM diagnostic targets. The methodologies included haemoxylin and eosin staining, immunofluorescence, in situ hybridization and quantitative PCR. The findings identified that morphology correlates with malignancy in GBM patient pathology. Immunofluorescence confocal microscopy revealed prominin-1 in pseudo-palisades adjacent to necrotic foci in both animal and human GBM. Evidence is presented for an ICAM-1 association with degenerating vasculature. Significantly elevated nuclear PARTICLE expression from in situ hybridization and quantitative PCR reflected its role as a tumor activator. GAS5 identified within necrotic GBM validated this potential prognostic biomolecule with extended survival. Here we present evidence for the stem cell marker prominin-1 and the chemotherapeutic target ICAM-1 in a glioma animal model and GBM pathology sections from patients that elicited alternative responses to adjuvant chemotherapy. This foremost study introduces the long non-coding RNA PARTICLE into the context of human GBM pathogenesis while substantiating the role of GAS5 as a tumor suppressor. The validation of GBM biomarkers from cellular models contributes to the advancement towards superior detection, therapeutic responders and the ultimate attainment of promising prognoses for this currently incurable brain cancer.
Keywords: prominin-1; Glioma; ICAM-1; U87MG; Eker rats; PARTICLE; Biomarker; GAS5; lncRNA; GBM